Atualizações audiovisuais do fotojornalismo na web - Canella, Vlademir (Universidade do Vale do Rio dos Sinos, 2016)
New media tense photojournalism practices and insert a media process itself when are updated in the web environment. The following pages, bring a map of photojournalism web, discussing the various ways in which these updates happen and trying to understand them as audiovisualidades. This is a world of buildings (KILPP, 2003) and imaging techniques (FLUSSER, 2002) or concepts of the world that are built technical, aesthetic and culturally. For this, we observe newspapers through their photojournalistic practices on the web and what these last (BERGSON, 2006), fundamentally. We pursue, at first, those common frames, which give meaning to press photography and also the web as a means; secondly, deepen the observation of such frames through dissection, where we then to the newspaper El País, Colombia and the multimedia section called Reportaje 360, which we found very elements of photojournalism, the internet and also the photojournalism as construct the web.
Keywords: Fotojornalismo; Audiovisualidades; Fotografia; Jornalismo; Web; Photojournalism; Photography; Journalism; ACCNPQ::Ciências Sociais Aplicadas::Comunicação